Airway and Feeding Outcomes in Pierre Robin Sequence: A Comparison of Three Management Strategies. (June 2023) - Khansa, Ibrahim; Aldabbeh, Summer; Pearson, Gregory D.; Baylis, Adriane; Madhoun, Lauren L.; Schoenbrunner, Anna; Splaingard, Mark; Kirschner, Richard E.
Background: Controversy remains regarding optimal management of Pierre Robin sequence (PRS). The goal of this study was to compare airway and feeding outcomes in infants with PRS who underwent surgical intervention, specifically mandibular distraction osteogenesis (MDO) or tongue-lip adhesion (TLA), or who had conservative management (CM) without surgery. Methods: All consecutive patients treated for PRS at a pediatric academic medical center, with at least one year follow-up, were included. Patients who underwent tracheostomy as an index procedure were excluded. Patients were divided into those who underwent MDO, TLA or CM. Feeding status and data from initial and follow-up polysomnograms were collected. Comparisons between groups were made using the Kruskal-Wallis test, followed by Mann-Whitney pairwise comparison with a Bonferroni correction, when appropriate. Results: 67 neonates were included. 19 underwent TLA, 29 underwent MDO and 19 underwent CM. The proportions of syndromic patients were similar between groups. Patients undergoing CM had the lowest baseline AHI (9.1), but there were no significant differences between TLA (20.1) and MDO (25.4). At follow-up, the three groups had similar mean AHI (MDO 1.3, TLA 4.2, CM 4.5). A similar proportion of patients achieved AHI 5 or less (TLA 89.5%, MDO 96.6%, CM 84.2%). At one year, there were no significant differences in weight percentiles or in risk of failure-to-thrive between groups. One patient from the TLA group required a tracheostomy. Conclusion: The three treatment modalities achieved high airway and feeding success rates. All three modalities should have a place in the armamentarium of the craniofacial surgeon.